2015
DOI: 10.1007/s13197-015-1956-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of sourdough fermented date seed for improving the quality and shelf life of flat bread: study with univariate and multivariate analyses

Abstract: The aim of this work was to study the effects of a novel sourdough system prepared by wheat flour supplemented by combination of pulverized date seed, Lactobacillus plantarum, and/or Lactobacillus brevis as well as Saccharomyces cerevisiae on the sourdough characteristics, quality, sensory, texture, shelf life and image properties of Barbari flat bread. The highest sourdough acidity and bread specific volume was obtained with co-culture of Lb. plantarum + Lb. brevis + S. cerevisiae. The results suggest that fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…All these virtues recognized by "conôro" could classify it as a functional food. Studies conducted on other condiments and species with significant socio-economic value in the sub-region confirm these findings (Fandohan et al, 2010;Kim et al, 2016;Najafi et al, 2016;Monyn et al, 2016). The study conducted among the populations revealed seven types of "conôro".…”
Section: Discussionsupporting
confidence: 60%
“…All these virtues recognized by "conôro" could classify it as a functional food. Studies conducted on other condiments and species with significant socio-economic value in the sub-region confirm these findings (Fandohan et al, 2010;Kim et al, 2016;Najafi et al, 2016;Monyn et al, 2016). The study conducted among the populations revealed seven types of "conôro".…”
Section: Discussionsupporting
confidence: 60%
“…However, a transglutaminase (TG) was used to increase fermentation stability [34]. It is thought that dough acidification could have a direct impact in gas cell formation and size by modifying the interaction between water and other molecules within the food matrix [35]. The decrease of G could be the best explanation for this.…”
Section: Physical Assaymentioning
confidence: 99%
“…The PLSR as a asymmetric method is particularly used to predict one data set from the other while PCA as a symmetric method only depicts the relationship between data sets (Martens and Martens, 2001). Several researchers have attempted to correlate various characteristics of different products (Najafi, Pourfarzad, Zahedi, Ahmadian-Koochaksaraei and Khodaparast, 2016; Hejri-Zarifi et al., 2013; Pourfarzad et al., 2012; Sai Manohar and Haridas Rao, 2002). PLSR was applied to examine the relationship between textural X and sensory Y data.…”
Section: Resultsmentioning
confidence: 99%